Sortir avec sa doctorante, un cas limite des relations sexo-affectives au travail - Farah Deruelle (Genre, Sexualité et Société)
This article proposes a critical examination of intimate relationships between thesis supervisors and doctoral candidates in the scientific research environmen. Based on a field study, it seeks to determine whether the prism of consent is sufficient to grasp the nature of the problem posed by this controversial type of asymmetrical relationships. To this end, it focuses on two case-study interviews in particular : one involving clear sexual harassment, the other taking place in a conjugal and a priori consensual setting. The analysis then shows that these relationships, which are permeated by pedagogy, desire and above all power, conceal numerous consequences in their day-to-day practice, both in terms of breaches of academics ethics and damage to the women’s careers. In this case, consent doesn’t change a thing.